Fundamentals of space law and policy - Tronchetti, Fabio (SpringerBriefs in Space Development, 2013)
Presents and addresses key space law and policy issues for the benefit of wider informed audiences that wish to acquaint themselves with the fundamentals of the space law field. This brief analyzes in a concise manner the combined influence of space law and policy on international space activities. Read in conjunction with the other books in the Springer 'Space Development' series, it supports a broader understanding of the business, economics, engineering, legal, and procedural aspects of space activities. This book will also give the casual reader as well as experts in the field insight on present and future space law and policy trends, challenges and opportunities.